Profile and Mapping of Tourism Destinations in Oma Village (Applied Research 1st Year) - Maudy M. Tanihatu; Marie. C. Tahalele; Ricardo. M Simarmata; Sammy Saptenno; Dian Utami Sutiksno (AIBPM Publisher, 2021)
The tourism sector is a service sector that contributes significantly financially to the country's economy. Maluku province has tourism potential. Including a tourist attraction in Oma village, one of the villages in Central Maluku district, Ambon City, Maluku Province. This research is a multi-year study (4 years) and aims to: 1. create a profile and mapping of tourist objects, 2. create easy access and facilities, 3. implement integrated marketing communications and digitization of tourism marketing and 4. collaborate on tourism marketing in Oma village with Maluku tourism & investment industry. For the first year of research, the research objective is number 1, which is to create a profile and mapping of tourist objects in Oma's Country. This type of research is applied research and qualitative methods. The results of this first year's research were successfully profiled and mapped tourist destinations. From the results of the research, it is known that there are still many things that must be addressed, and continued in the second research stage and so on.